Clinical-grade plant-made nanomaterials: from process design to the construction of a manufacturing facility - Pivotto, Denise; Rosa, Anthony; Elsheikh, Aya Maged; Gecchele, Elisa; Zampieri, Roberta; Raneri, Alessia; Garonzi, Valentina; Avesani, Linda (Frontiers in Plant Science, 2026)
Plant-made nanomaterials are proteinaceous elements that are emerging as multi-purpose and versatile tools in the therapeutic landscape. In the context of autoimmune diseases, Tomato Bushy Stunt Virus (TBSV) has been previously explored as a platform for inducing immune tolerance by displaying disease-specific immunodominant peptides—offering a potential path toward disease remission. In this study, we developed a dedicated facility and a Good Manufacturing-compliant Process for producing TBSV-based nanoparticles engineered to display peptides relevant to specific autoimmune disorders. Data collected from multiple non-consecutive pilot-scale production batches were used to build a simplified techno-economic model of the process. The process is readily scalable and offers opportunities for further improvements, supporting the potential to meet market demands for early-stage therapeutic interventions in autoimmune diseases. Additionally, a preliminary Environmental, Health, and Safety (EHS) assessment of the process showed a highly favorable environmental output index and minimal associated risks, reinforcing the platform’s sustainability. These results support the viability of plant-based manufacturing for therapeutic nanomaterials and highlight TBSV’s potential as a novel platform for tolerance-inducing treatments in autoimmune diseases.